2015
DOI: 10.1007/s40336-015-0127-x
|View full text |Cite
|
Sign up to set email alerts
|

Current status of FDG-PET/CT in staging of adult lymphoma

Abstract: Staging defines disease location and extent, suggests prognostic information and provides a baseline against which response or disease progression can be compared. Studies in Hodgkin (HL) and non-Hodgkin lymphoma (NHL) generally conclude that PET/CT is more accurate for diagnosing both nodal and extranodal disease than computed tomography (CT), thus having a strong potential impact on the staging of these lymphomas. Due to the high sensitivity and specificity of PET/CT in detecting bone marrow disease in newly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 93 publications
0
3
0
Order By: Relevance
“…FL is an FDG-avid disease in more than 95% of the cases. PET/CT is recommended for baseline staging by international guidelines, as it is able to detect nodal and most of all extranodal disease, including bone marrow, with a superior sensitivity (93%) and specificity compared to a CeCT, thus being able to upstage a significant proportion of the CeCT-staged patients and to ensure a more appropriate treatment for them (34,45,46). PET/CT was also useful to suspect a histological transformation to high-grade lymphoma, based on an elevated value of the maximum Standardized Uptake Value (SUVmax).…”
Section: Role Of Pet/ct Imaging In Follicular Lymphomamentioning
confidence: 99%
“…FL is an FDG-avid disease in more than 95% of the cases. PET/CT is recommended for baseline staging by international guidelines, as it is able to detect nodal and most of all extranodal disease, including bone marrow, with a superior sensitivity (93%) and specificity compared to a CeCT, thus being able to upstage a significant proportion of the CeCT-staged patients and to ensure a more appropriate treatment for them (34,45,46). PET/CT was also useful to suspect a histological transformation to high-grade lymphoma, based on an elevated value of the maximum Standardized Uptake Value (SUVmax).…”
Section: Role Of Pet/ct Imaging In Follicular Lymphomamentioning
confidence: 99%
“…Remaining one-third of NHL present with symptoms associated with involvement of extra nodal sites like skin, stomach or brain. Treatment strategy of lymphoma depends upon the staging of disease which defines disease location, extension, suggests prognostic information and provides a baseline against which treatment response or disease progression can be compared (3). Accurate staging can minimize the therapeutic toxic effect and reduces the morbidity and mortality associated with therapy.…”
Section: Introductionmentioning
confidence: 99%
“…PET/CT has already been a fundamental tool for staging and restaging in lymphoma [ 3 , 4 ] and its use is now standardized in the so-called Lugano criteria [ 5 ]. Recently, several clinical trials demonstrated that treatment could be guided by PET/CT also during the treatment itself, changing the ongoing therapy based on its results [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%